Minimax rate in prediction for functional principal component regression. Issue 5 (4th March 2021) - Yang, Guangren; Lin, Hongmei; Lian, Heng
Abstract: In this short paper, we consider the convergence rate of functional linear regression in prediction loss. For upper bound we consider estimation of the slope function based on functional principal component analysis. Lower bound is also obtained that shows the convergence rate obtained using functional principal component regression is optimal.